Characterization of rutile passivation layers formed on Magnéli-phase titanium oxide inert anodes - Rowles, Matthew; Scarlett, N.; Madsen, I.; McGregor, K. (IUCr Journals, 2011)
An ex situ characterization study has been performed on rutile passivation layers on inert anodes used for molten salt electrochemical studies. Rutile layer thicknesses were estimated using a number of ex situ methods, including laboratory and synchrotron X-ray diffraction and optical microscopy. The only phases in the anode detected by diffraction were the Magnéli phases (TinO2n-1, n = 5-6) of the unreacted anode and rutile (TiO2), which forms on electrolysis. These measurements validate a previously developed in situ energy-dispersive X-ray diffraction analysis technique [Scarlett, Madsen, Evans, Coelho, McGregor, Rowles, Lanyon & Urban (2009). J. Appl. Cryst. 42, 502-512].